Exploring the Impact of Thermal Environment on Student Well-Being in Sustainable Campus Settings - Khaula Alkaabi; Kashif Mehmood; Saif Bin Hdhaiba; Sarah Aljaberi; Noora Alkaabi (Applied Sciences)
As universities strive to create sustainable and comfortable learning environments, understanding the factors that influence student well-being is crucial for promoting good health and well-being (SDG 3) and fostering sustainable communities (SDG 11). This study, conducted at a female campus in the UAE, investigates the impact of various external factors on students’ psychological perceptions. Specifically, it examines how abaya color, landscape settings, and time of day affect body fatigue, eye fatigue, and thermal discomfort, providing valuable insights for campus planning and design. Using GrADS and an FLIR thermal camera, this research analyzed temperature, humidity, and surface temperatures. The Kruskal–Wallis test and Don Bonferroni pairwise comparisons were employed to assess the impact of conditions on psychological perceptions. The results indicate that abaya color insignificantly affected perceptions in summer, but light brown was preferred in spring. Landscape sites influenced eye fatigue and skin dryness in summer, favoring shaded areas. The time of day affected body heat, skin dryness, and thermal discomfort, with greater discomfort in summer afternoons. These findings offer valuable insights for campus planning, particularly in hot summer months, promoting students’ psychological well-being (SDG 3) and sustainable campus communities (SDG 11).